2001
DOI: 10.1002/rcm.554
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular cross‐linking experiments on cytochrome c and ribonuclease A using an isotope multiplet method

Abstract: Mass spectral analysis of tryptic digests of cross-linked proteins offers considerable promise as a simple technique to probe protein structure and study protein-protein interactions. We describe the use of a 1:1 mixture of isotopically labeled and unlabeled cross-linkers, disuccinimidyladipate (DSA) and dimethyladipimidate (DMA), to enhance visualization of cross-linked peptides in a tryptic digest. Optimized intramolecular reactions of cytochrome c and ribonuclease A (RNase A) with DSA yielded an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
135
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 16 publications
(31 reference statements)
1
135
0
1
Order By: Relevance
“…Improvement in mass spectrometry (MS) technology has made this conceivable, in particular high mass precision spectrometers and the development of isotopically coded cross-linkers [3][4][5] . Several studies have proven the general feasibility of this approach 3,[6][7][8][9] . Nonetheless, this methodology has only been used for single proteins or small, purified protein complexes so far.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in mass spectrometry (MS) technology has made this conceivable, in particular high mass precision spectrometers and the development of isotopically coded cross-linkers [3][4][5] . Several studies have proven the general feasibility of this approach 3,[6][7][8][9] . Nonetheless, this methodology has only been used for single proteins or small, purified protein complexes so far.…”
Section: Introductionmentioning
confidence: 99%
“…Person, et al, previously reported adduction by both benzoquinone and glutathione-S-yl-1,4-benzoquinone at sites K 86 and K 87 on cytochrome C, suggesting this is a highly reactive region of the protein (23,24). Pearson, et al, in a study of protein crosslinking agents, also observed reaction at the corresponding locus on bovine cytochrome C, although they declined to speculate on the reasons for activity at these positions (25). Person and co-workers suggest that the enhanced reactivity may reflect conformational flexibility, since lysines 86 and 87 are in loop regions of the protein (23), but this would not explain why only DODE appears to react at these positions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by another group using proteolytic digests to localize the cross-links in cytochrome-c, only one cross-link was observed with lysine reactive crosslinkers when the reaction was optimized to yield a single cross-link per protein molecule [9]. At higher cross-linker concentration optimized to yield two crosslinks per protein molecule, the digest yielded only four additional cross-links.…”
mentioning
confidence: 99%